NITROGEN MICROANALYSIS OF GLASS INCLUSIONS IN CHONDRITIC OLIVINES BY NUCLEAR REACTION - Varela M.E.; Mosbah M.B.; Kurat G.; Gallien J.P. (My University, 2003)
Measured were the abundance and distribution of nitrogen in glasses of glass inclusions in olivines of CV3, CO3, CR, C4, CH3, and LL chondritic meteorites by means of the 14N(d, p)15N nuclear reaction. Similar to what was observed with carbon, nitrogen is present in low concentrations (<20 ppm) in the structure of olivines but can by stored in variable amounts in glasses of glass inclusions. These primitive glasses, characterized by a Si-Al-Ca-rich composition, have highly variable nitrogen contents (30 to 1500 ppm) and highly inhomogeneous nitrogen distribution. Nitrogen contents are independent of the chemical composition of the glasses. The heterogeneous distribution is a common feature of all studied inclusions, as is evidenced by the variable contents of nitrogen in glass inclusions occurring in the same olivine grain. Nitrogen heterogeneity is suggestive of trapping of solid nitrogen carrier phases during formation of the constituents of chondrules. However, part of the originally trapped nitrogen appears to have been lost, possibly, by ulterior oxidation and subsequent transformation into volatile species.